ESTUDOS EM EFICIÊNCIA ENERGÉTICA NAS RESIDÊNCIAS - Jarczeski, Bruno Gustavo; Alves, Leonardo Camera; Backes, Letícia Raquel; De Souza, Paulo Ricardo Petzold; Maschio, Felipe Bentz; Enderle, Taciana Paula Enderle (Salão do Conhecimento, 2018)
Pesquisa desenvolvida no Grupo de Estudos de Eficiência Energética